ANALISA BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN LABA PADA UD. BATAKO PRESS WAITATIRI RAYA - Revelino Tamaela; Sammy Saptenno; Febiola Matuankotta (P3M Politeknik Negeri Ambon, 2025)
Break Even Point Analysis (BEP) or commonly referred to as the Break Even Point is used to determine the production price or level of sales made by a company. Thus, a company can be at the Break Even Point where it does not experience profit or loss. The purpose of this study is to determine the number of units that must be produced, the profit target of 20% in 2021 and the Margin of Safety at UD. Batako Press Waitatiri Raya. From the results of research and discussion, it is known that the minimum sales volume in units that must be produced by UD. Batako Press Waitatiri Raya amounted to 73.850. Then, the level of sales in rupiah that must be done to get 20% profit in 2021 is Rp. 464.782.500,00 and the Margin of Safety presentation obtained is 61%. From the results of the calculation of the break-even point by planning a profit of 20%, so that UD. Press Waitatiri Raya bricks must sell for Rp. 464.782.500.00 then UD. Batako Press Waitatiri Raya will achieve the profit from the sales target, otherwise if the sales are below the target, the profit will not reach 20%. Then, the Margin of safety presentation should not fall more than 61%. If sales are still around 61% or the maximum decline does not exceed 61%, it can be concluded that the company is still said to be safe or not experiencing losses.